The Influence of Workload and Employee Compensation on Job Satisfaction of Warehouse Employees at PT Adis Dimension Footwear Tangerang Regency - Fadillah, Deva Tri; Hia, Era Era; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the influence of workload and compensation on job satisfaction of warehouse employees at PT Adis Dimension Footwear, Tangerang Regency.This study employed a quantitative descriptive method, which describes variables as they are, supported by numerical data derived from actual conditions. The population in this study was all production employees at PT Adis Dimension Footwear, Balaraja, Tangerang. The sample size was 50 respondents. This study used a saturated sampling technique due to the small population size; therefore, the entire population of 50 employees was used as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis using SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, workload significantly influences the job satisfaction of Ware House employees at PT Adis Dimension Footwear, Tangerang Regency, which is indicated by the calculated t value > t table (8.005 > 2.012) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, compensation significantly influences the job satisfaction of Ware House employees at PT Adis Dimension Footwear, Tangerang Regency, which is indicated by the calculated t value > t table (2.500 > 2.012) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, workload and compensation significantly influence the job satisfaction of Ware House employees at PT Adis Dimension Footwear, Tangerang Regency, which is indicated by F count > F table (78.062 > 3.19) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected.Based on the research results, it can be concluded that workload and compensation variables, both partially and simultaneously, have a significant influence on job satisfaction of Warehouse employees at PT Adis Dimension Footwear, Tangerang Regency.